Stereoselectivity ratios in a simple Diels-Alder reaction in aqueous salt solutions of alcohols - Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron, 2005)
This is the first exhaustive report on the variation of stereoselectivity ratios for a simple Diels-Alder reaction between cyclopentadiene and methyl acrylate. The reaction was carried out in aqueous mixtures of methanol, ethanol, propan-1-ol and butan-1-ol in presence of LiClO4, LiCl, NaCl, KCl, CaCl2 and MgCl2. The endo sterecisomer decreases with the increase in carbon chain length of the alcohol. However, LiClO4, a salting-in agent in water becomes salting-out in aqueous mixtures of alcohols. The solvent properties, thus can be attuned by adjusting the amount of solvents and salts. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: aqueous alcohols; Diels-Alder reaction; endolexo ratios; salts

Solubilization and conformational behavior of zein in aqueous solution of dodecyldimethylethylammonium bromide (DDAB) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2009)
The solubilization and conformational behavior of Zein in the presence of cationic surfactant, dodecyldimethylethylammonium bromide (DDAB) have been studied. The colloidal properties of DDAB in the absence and presence of Zein have also been investigated using physico-chemical and spectroscopy methods. The surfactant appears to bind to Zein at concentrations below the critical micelle concentration (cmc) and the binding becomes weaker at concentrations above the cmc. The interaction between DDAB and Zein depends on the chemical structure and molecular parameters (conformation, molar mass, charge) of the protein. The schematic sketches of the molecular mechanisms of the complex formation between like-charged proteins and surfactants have been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Absorbance spectroscopy; Aggregation number; conductivity; DDAB; FT-IR; Surface tension; viscosity; Zein

Solvent-induced viscosity changes in ionic liquids - a review - Khupse, Nageshwar D.; Kumar, Anil (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2010)
The high viscosity of several ionic liquids is an undesirable property for their applications in a variety of chemical reactions and electrochemical devices. Addition of a solvent in an ionic liquid is known to reduce its high viscosity to a great extent. In this review, an attempt has been made to examine the published data on the reduction in viscosities of many ionic liquids upon the addition of molecular solvents, including water. A tentative description has been provided for the drop in viscosities under these conditions. Analysis of the viscosity data with the help of empirical equations has been summarized. This critical review also outlines the future outlook of the required studies that might be useful to those who are interested in using ionic liquids for a variety of applications.
Keywords: ionic liquids; solvent; viscosity

Solvent-mediated molar conductivity of protic ionic liquids - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The molar conductivity, A(m), of protic ionic liquids (PILs) in molecular solvents is measured at 298.15 K. The decrease in the A(m) values of PILs is observed with an increase in the concentration of PILs. The limiting molar conductivities, A(m)(0), were obtained for each PIL in different molecular solvents using a least squares method. The A(m)(0) data for PILs were correlated with the structural aspects of PILs and solvent properties. The polar protic solvents show poor ionic association as compared to the polar aprotic solvents, which is discussed on the basis of the hydrogen bond donating (HBD) ability of solvents and PILs. The alkyl chain substitution of anions plays a significant role in the ionic association of the PILs. The diffusion coefficient D-0 and the transport number t were determined, which were consistent with the A(m)(0) values of PILs in water. The A(m)(0) and D-0 values are dependent on the hydrodynamic radius of anions of these ionic liquids. The extent of ionic association for each PIL was discussed using temperature dependent A(m) data for aqueous PIL systems in terms of the Walden plot.

Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Spectacular rate enhancement of the diels-alder reaction at the ionic liquid/n-hexane interface - Beniwal, Vijay; Manna, Arpan; Kumar, Anil (Chemphyschem, 2016)
The use of the ionic liquid/n-hexane interface as a new class of reaction medium for the Diels-Alder reaction gives large rate enhancements of the order of 10(6) to 10(8) times and high stereoselectivity, as compared to homogeneous media. The rate enhancement is attributed to the H-bonding abilities and polarities of the ionic liquids, whereas the hydrophobicity of ionic liquids was considered to be the factor in controlling stereoselectivity.
Keywords: Diels-Alder reaction; Interfaces; ionic liquids; kinetics; stereoselectivity